The Role of Parents in Shaping Children’s Character during Online Learning during the Pandemic Period at MI Muhammadiyah Butuh 2 - Mufida, Lailatul; Imron, Imron (Prosiding University Research Colloquium, 2021)
This study aims to find out how big the role of parents in shaping the character or personality of children when they study at home during this pandemic. The pandemic that has occurred in Indonesia has been going on for more than a year. This is certainly a challenge for parents who have children at school age. Children will interact more often with their families when they ask their parents for help when doing their schoolwork. When they interact, namely between parents and children, parents must be ready to face challenges. The challenge is how they instill the morals of children towards their parents, when they interact in learning because usually children will underestimate their parents more than their teachers when they study. Most parents think that learning with their parents is certainly more difficult than with the teacher, of course, in terms of character building. If with the teacher the child will tend to be more obedient, more respectful, more appreciative, etc. The research method chosen is a qualitative method. Data collection techniques used in the form of observations and interviews with a number of parents who have children at school age. The results of the study show that the attitude of children when they study with their parents is very concerning. There are still many who often show disrespectful attitudes when studying with their parents. This is acknowledged by some parents who sometimes often fight with their children when they study at home. Based on the results of the study, it can be concluded that the influence of parents in instilling children’s character during a pandemic is very large. As a parent, you should be more assertive when the child has done things that are not in accordance with his character. In this case the cultivation of children’s character should also be monitored and supervised by the teacher.